2005
DOI: 10.1152/jn.00714.2004
|View full text |Cite
|
Sign up to set email alerts
|

Early Alcohol Exposure Induces Persistent Alteration of Cortical Columnar Organization and Reduced Orientation Selectivity in the Visual Cortex

Abstract: Fetal alcohol syndrome (FAS) is a major cause of learning and sensory deficits in children. The visual system in particular is markedly affected, with an elevated prevalence of poor visual perceptual skills. Developmental problems involving the neocortex are likely to make a major contribution to some of these abnormalities. Neuronal selectivity to stimulus orientation, a functional property thought to be crucial for normal vision, may be especially vulnerable to alcohol exposure because it starts developing e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
66
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(71 citation statements)
references
References 70 publications
(83 reference statements)
5
66
0
Order By: Relevance
“…It is possible that ethanol-induced activation of G9a and histone H3 modification during development disrupts the specific process involved in refinement of neuronal circuits, which leads to persistent synaptic dysfunction in adulthood. This could explain why some cortical maps (Margret, et al, 2006, Medina, et al, 2005, Powrozek and Zhou, 2005, Zhou, et al, 2005) and olfacto-hippocampal networks (Sadrian, et al, 2012, Wilson, et al, 2011) are altered in FASD models. Moreover, G9a-deficient mice display signs of severe developmental growth retardation and generally die between the embryonic days 9.5 and 12.5 (Tachibana, et al, 2002, Tachibana, et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that ethanol-induced activation of G9a and histone H3 modification during development disrupts the specific process involved in refinement of neuronal circuits, which leads to persistent synaptic dysfunction in adulthood. This could explain why some cortical maps (Margret, et al, 2006, Medina, et al, 2005, Powrozek and Zhou, 2005, Zhou, et al, 2005) and olfacto-hippocampal networks (Sadrian, et al, 2012, Wilson, et al, 2011) are altered in FASD models. Moreover, G9a-deficient mice display signs of severe developmental growth retardation and generally die between the embryonic days 9.5 and 12.5 (Tachibana, et al, 2002, Tachibana, et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…These typical amblyogenic precursors were not evident in our sample of children with FASD. However, research with animal models by Medina et al 10,30 showed that early alcohol exposure adversely affects the development of ocular dominance columns and neuronal orientation selectivity within the visual cortex. They exposed ferrets to alcohol from day P10 to P30, a postnatal period equivalent to the last trimester of human gestation, and assessed the effects at P48 to P65 when orientation selectivity in normal ferret cortex is mature.…”
Section: Discussionmentioning
confidence: 99%
“…This may have profound implications for developing fetuses, in which it has been demonstrated in animal models of fetal alcohol syndrome that exposure to alcohol leads to a variety of neuropathologies, including alterations in the developing visual system (Stromland, 2004) such as a profound loss of plasticity in visual cortex (Medina et al, 2005). Understanding the susceptibility of developing networks to neuromodulatory substances will provide insights into the mechanisms by which exposure to substances such as alcohol impact the prenatal wiring of the nervous system.…”
Section: Implications For Fetal Developmentmentioning
confidence: 99%